2xa+xb+7=11

Simple and best practice solution for 2xa+xb+7=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2xa+xb+7=11 equation:


Simplifying
2xa + xb + 7 = 11

Reorder the terms:
7 + 2ax + bx = 11

Solving
7 + 2ax + bx = 11

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + 2ax + -7 + bx = 11 + -7

Reorder the terms:
7 + -7 + 2ax + bx = 11 + -7

Combine like terms: 7 + -7 = 0
0 + 2ax + bx = 11 + -7
2ax + bx = 11 + -7

Combine like terms: 11 + -7 = 4
2ax + bx = 4

Add '-1bx' to each side of the equation.
2ax + bx + -1bx = 4 + -1bx

Combine like terms: bx + -1bx = 0
2ax + 0 = 4 + -1bx
2ax = 4 + -1bx

Divide each side by '2x'.
a = 2x-1 + -0.5b

Simplifying
a = 2x-1 + -0.5b

Reorder the terms:
a = -0.5b + 2x-1

See similar equations:

| 40=3y-11y | | 2/3(1/2-(-3/2)(-2/3) | | 8x-x=-14 | | -b+9=10b | | 6z-20=-22+7z | | 9p-19=-18+8p | | 2x-d=2x+4 | | 16(6)-1= | | 5(6)+9= | | 3r=105s | | 3x/y=3 | | 11d+9d+12=5d+28 | | 9(6)+2= | | F(7)=3x | | 6y-(3y+10)=0 | | 5(7)=3x | | 4(x-5)=-28+4x | | 1-5(x+7)=-5x-34 | | 5(3+4)-2=93 | | 9y+2+5y+9=16y-1 | | -2-4(-8x-3)=-246 | | 10/r=5/3 | | 2x+1+x-3+100+3X-2=360 | | 2x+1+x-3+100+3X-2=369 | | -5-(3*5-2)=-5-13 | | 3-8r=96 | | w=2l+2w-2l | | ax+bx=5 | | 12-6(3x-4)=-6 | | 0=15x | | 3x-63=-7x+27 | | 6x-5(6x)=272 |

Equations solver categories